Prevalence of Soft Tissue and Bone Tumor Diagnostic Discrepancies from Initial to Referral Sarcoma Center - Khomsit Thongthammachat; Sorranart Muangsomboon; Akarin Nimmannit; Charuwan Akewanlop; Chandhanarat Chandhanayingyong; Rapin Phimolsarnti; Jomjit Chantharasamee (Siriraj Medical Journal)
Objective: Diagnosing sarcoma can be challenging. This study evaluates pathological reviews of all sarcoma cases diagnosed at Siriraj Hospital, comparing initial diagnoses with those confirmed by a dedicated sarcoma pathologist